The principles of child-centred migrant integration policy - Gornik, Barbara (Annales. Series historia et sociologia, 2020)
The article looks at a child-centred approach to the integration of migrant children and discusses the principles of such an approach in the practice of policy-making. It argues that any child-centred policy must aim at fulfilling the fundamental participatory rights of children, in particular the right to be heard and express their views as basic functioning legal principles and underlying assumptions. The article develops a framework for the child-centred integration policy as one that builds on the knowledge gained through the child-centred approach, focuses on the current well-being of children, supports the participation of children in a broader social context, ensures the involvement of children in policy development, is defined with policy flexibility and follows the principles of child-centred education.
Keywords: child-centred approach; children participation; education; integracija; integracijska politika; integration; integration policy; migracije; migrant children; migration; otrokosrediščni pristop; participacija otrok; priseljeni otroci; vključevanje